LITHUANIAN EXPERIENCE REGULATING CONFLICT OF INTEREST: BALANCING ON PRIVATE AND PUBLIC EDGE - Palidauskaitė, Jolanta (Politologija, 2015)
The situation of conflict of interest may appear in activity of every professional irrespective of affiliation to public, private or nongovernmental sector. The consequences of conflict of interests is biased, subjective and nontransparent decision, improper fulfillment of prescribed duties, falling standards and decreased public trust not just in politicians or civil servants but in public institutions and government. The notion of conflict of interests varies but in this paper the following definition is used. Conflict of interest is a situation in which a person (in this paper politician or public official) has a private or other interest which is such as to influence, or appear to influence, the impartial and objective performance of his / her official duties. Research of this problem can be described as moving from legalistic towards more general understanding. The topic is interdisciplinary and can be analyzed from the political science, public administration, ethics or management perspective. Analyses of the practice allowed researchers to distinguish the third type of such conflict of interest – the apparent conflict-to the existing or potential conflict of interests. Development of society and changed surrounding of government activity increased the potential risk areas (gift giving, hospitality, bribery, contracts, trading information, etc.) for such situation to appear. In the past few decades increasing perceptions of falling ethical standards in legislatures, executive or ordinary public officials activity (scandals, misbehavior) have led in many advanced democracies to the introduction of ethics frameworks for elected or appointed officials. In order to give priority to public interest and properly perform public duties some regulation can be applied. 1) Prohibitions on the performance of certain functions, and/or the holding of certain positions or certain interests by public officials. 2) The establishment of duties of public officials to declare interests they have, either generally or in specific cases. 3) Exclusion or self-exclusion of public officials from participation in decision-making processes or matters where they are subject to a conflict of interest. These regulations are generally established and implemented through three main instruments: civil service legislation, conflict of interest legislation and codes of ethics / codes of conduct. The historical development of Lithuanian society in XIX and XX century was not in favor to develop clear sense of drawing the line between public and private interest but during the interwar Lithuanian Republic period few attempts to prohibit such conflict of interest were taken. The legislation prohibited holding a few offices and to employ relatives. Some current Lithuanian legislation directly some indirectly (Public Service Act, Seimas’ Statute, etc.) try to control similar situation which may turn into corrupt acti-vity or misuse of public office for private or other interests. The first special legislation prohibiting conflict of interests was issued in 1997. The Law on the Compatibility of Public and Private Interests in the Public Service underwent three main corrections. The analysis of this legislation allows concluding that the main weakness was not corrected. The usage of the term “adjust” instead of “separation” might be understood as a compromise instead of taking the stricter position dealing with the issue. The Law seeks “to adjust private and public interests, to ensure that priority is given to public interests, to strengthen impartiality of decisions and to prevent corruption in public service” and applies to both public servants and politicians. Meanwhile in other countries legislative has more ambitious goal to ensue public interest priority. The analyses of seventeen codes of ethics and codes of conduct existing in various Lithuanian public institutions showed that their authors paid some attention to this issue. Some codes refer to existing legislation; some describe general principles for conduct or try to explain how to behave in such uneasy situations. There are fundamental differences between elected officials and civil servants which have major implications for conflict of interest regulation first of all due to their different roles, term of service. Some Lithuanian legislation regulating conflict of interests apply to politicians and civil servants, some differ. As in other democracies activity of civil servants are more regulated (Public service act, law on Public administration, Ethical rules of conduct, etc.). But existing legislation does not change the situation and can not increase public trust if is not understood and properly implemented.